Proceedings of OCEANS '93
DOI: 10.1109/oceans.1993.326187
|View full text |Cite
|
Sign up to set email alerts
|

Textural analysis and structure-tracking for geological mapping: applications to sonar images from Endeavour Segment, Juan de Fuca Ridge

Abstract: Abshoet-'The volume of data collected by slde-scan sonar during seafloor surveys has become larger and larger as the resolution of th-systems has Improved. As a result, new Image p " i n g techniques need to be developed to partly automate the interpretation d thls increasing wealth of data. "he 6mt two steps In the geological analysis of a new image usually are t h mapplng of W a r structures, and d morphologic units. These maps are then used In tectonk a d geologlcpl Interpretations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…This shows that the textural entropy and homogeneity, computed with GLCMs in moving windows of 20U20 pixels, best describe the texture and image variability. This is consistent with previous analyses performed on similarly high-resolution sidescan sonar imagery, like DSL-120 data (1-m resolution : Blondel et al, 1993) or TOBI data (6-m resolution : Blondel, 1996). The technique and its results are detailed in 4.…”
Section: Spatial Statistics and Image Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…This shows that the textural entropy and homogeneity, computed with GLCMs in moving windows of 20U20 pixels, best describe the texture and image variability. This is consistent with previous analyses performed on similarly high-resolution sidescan sonar imagery, like DSL-120 data (1-m resolution : Blondel et al, 1993) or TOBI data (6-m resolution : Blondel, 1996). The technique and its results are detailed in 4.…”
Section: Spatial Statistics and Image Analysissupporting
confidence: 90%
“…Textures can be quanti¢ed in di¡erent ways, but theoretical work by Haralick (1979) and practical applications to sonar imagery by Reed and Hussong (1989), Blondel et al (1993), Blondel (1996,2000), Gao et al (1998) and others have shown that co-occurrence matrices are the most adapted tools. Co-occurrence matrices address the average spatial relationships between pixels of a small region.…”
Section: Textural Analysismentioning
confidence: 99%
“…The distance and angle for the examined pixels whose spatial relationship was displaced was set to 1 pixel and 0°, 45°, 90°, or 135°. Blondel et al [1993] and Blondel [1996] suggested that two textural features of homogeneity and entropy were sufficient for side-scan sonar interpretation among many textural features [e.g., Haralick et al, 1973]. In addition to these two features, we included a textural feature called correlation in the process of classification to obtain better results, as described later.…”
Section: Classification Using Glcmmentioning
confidence: 99%
“…To complement visual inspection of sonar images, we also provide a seafloor classification system generated from textural analysis by means of grey level cooccurrence matrix (GLCM) using the calibrated sonar data. This technique has been successfully applied for marine geophysical and geological surveys and habitat mapping [e.g., Reed and Hussong, 1989;Gao et al, 1998;Blondel et al, 1993;Blondel, 1996Blondel, , 2000Hurst and Karson, 2004;Mitchell and Clarke, 1994;Cochrane and Lafferty, 2002;Huvenne et al, 2002]. In this study, calibrated backscattering levels were effectively incorporated in the classification, which was often not possible in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…(1) short-run emphasis (SRE) This concept is also known by other names, such as greytone spatial-dependence matrices (Haralick et al 1973) and grey-level co-occurrence matrices (Weszka et al 1976;Pace & Dyer 1979;Reed & Hussong 1989;Blondel et al 1993). Haralick et al (1973) considered an image of nxn pixels quantised to M grey levels.…”
Section: Grey-level Run-length Featuresmentioning
confidence: 99%